Las fake news o noticias falsas vulneran el derecho al honor y buen nombre de los ciudadanos al no estar instituidas como un tipo penal en el COIP. - Morales Carrión, Ronald David (2023)
The present work arises in response to the need to study one of the problems that have become more pronounced in recent years: the dissemination of fake news. This situation has gained ground among citizens, who are freely exposed to the use of information technologies. Similarly, it is related to the lack of legal control that allows for the regulation of the content published by the media, so it is currently not possible to ensure that the information is truly truthful. In light of this situation, the objective is to carry out a doctrinal and comparative legal study on fake news that infringe upon the right to honor and good reputation. These types of behaviors, despite violating constitutional rights, have become normalized due to their repetition and the fact that they are not classified as a crime in the Comprehensive Organic Penal Code. In this regard, in order to conduct the investigation, an analysis of related topics was carried out to understand how fake news and doctrine have evolved over the years. Likewise, surveys and interviews were conducted with various legal actors in the city of Loja in order to gather their perspectives on this issue. Thus, it was possible to corroborate the urgent need to include the crime of disseminating fake news in the Comprehensive Organic Penal Code, as it is a method used to violate citizens' rights. Therefore, a reform proposal for this code was established, which can be taken into account for formal implementation in the country.